2022
DOI: 10.1038/s41418-022-00938-9
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 auto-cleavage regulates programmed cell death and collaborates with RIPK3/MLKL to prevent lymphopenia

Abstract: Caspase-8 is an initiator of death receptor-induced apoptosis and an inhibitor of RIPK3-MLKL-dependent necroptosis. In addition, caspase-8 has been implicated in diseases such as lymphoproliferation, immunodeficiency, and autoimmunity in humans. Although auto-cleavage is indispensable for caspase-8 activation, its physiological functions remain poorly understood. Here, we generated a caspase-8 mutant lacking E385 in auto-cleavage site knock-in mouse (Casp8ΔE385/ΔE385). Casp8ΔE385/ΔE385 cells were expectedly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…RTECs will undergo multiple modalities of cell death during AKI. To determine the cell death pathway that was most affected by loss-of-DUSP2, we firstly extensively analyzed the executioners of apoptosis ( Caspase3 ), necroptosis ( Mlkl and Ripr3 ), ferroptosis ( Gpx4 and Slc7a11 ), and pyroptosis ( Casp1 and Gsdmd ) in RTECs 31 - 35 . Interestingly, comparing to IRI/ Dusp2 fl/fl mice, we found that only the executioner of pyroptosis ( Gsdmd ) was significantly upregulated in RTECs of IRI/ Dusp2 CKO mice (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…RTECs will undergo multiple modalities of cell death during AKI. To determine the cell death pathway that was most affected by loss-of-DUSP2, we firstly extensively analyzed the executioners of apoptosis ( Caspase3 ), necroptosis ( Mlkl and Ripr3 ), ferroptosis ( Gpx4 and Slc7a11 ), and pyroptosis ( Casp1 and Gsdmd ) in RTECs 31 - 35 . Interestingly, comparing to IRI/ Dusp2 fl/fl mice, we found that only the executioner of pyroptosis ( Gsdmd ) was significantly upregulated in RTECs of IRI/ Dusp2 CKO mice (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…and mitogen-activated protein kinase (MAPK) signaling pathways, inhibiting caspase-8 activation and promoting cell survival (72, [78][79][80]. If TNF-a recruits TRADD, FADD, procaspase-8, and RIPK1 to form complex iia, then complex iia promotes activation of caspase-8, and activated caspase-8 undergoes apoptosis by activating caspase-3 (73,81,82). When caspase-8 is inhibited or its activity level is relatively low, RIPK1 recruits RIPK3 and both recruit MLKL through the RIP homotypic interaction motif (RHIM) to form complex iib, also known as necrosome (83,84).…”
Section: Regulatory Mechanisms Of Necroptosismentioning
confidence: 99%
“…After TNF-α interacts with TNFR, TNFR1 starts to recruit the downstream protein molecules TNFR1- associated death domain protein (TRADD), RIPK1, TRAF2/5, and linear ubiquitin chain assembly complex (LU⁃BAC) proteins to form complex I, in which RIPK1 is polyubiquitinated and activates nuclear RIPK1 polyubiquitinates and activates the nuclear factor κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways, inhibiting caspase-8 activation and promoting cell survival ( 72 , 78 80 ). If TNF-α recruits TRADD, FADD, pro–caspase-8, and RIPK1 to form complex iia, then complex iia promotes activation of caspase-8, and activated caspase-8 undergoes apoptosis by activating caspase-3 ( 73 , 81 , 82 ). When caspase-8 is inhibited or its activity level is relatively low, RIPK1 recruits RIPK3 and both recruit MLKL through the RIP homotypic interaction motif (RHIM) to form complex iib, also known as necrosome ( 83 , 84 ).…”
Section: Necroptosismentioning
confidence: 99%
“…Presently, apoptosis is recognized as an immunologically silent cell death as this kind of cell elimination exhibits little risk to the host and occurs without activating inflammatory molecules . Conversely, cell death via necroptosis releases DAMPs, further inducing inflammation and organic detriment. …”
Section: Introductionmentioning
confidence: 99%
“…9 In the alternate scenario, caspase 8 cleaves RIPK1 and activates caspase 3, thereby inducing apoptosis. 10 After MLKL is phosphorylated by RIPK3 and forms oligomers as the executor of necroptosis, oligomeric MLKLs translocate to the plasma membrane to induce cell rupture either by recruiting Ca 2+ and Na + ion channels to disrupt the balance between intracellular and extracellular osmotic pressures 11 or by directly disintegrating the membrane through the pore structure of the oligomer. 12 In addition to RIPK1, two more proteins with RHIM domains, Z-DNA-binding protein 1 (ZBP1; also known as DAI or DLM-1) and toll-interleukin-1 receptor (TIR)-domaincontaining adapter-inducing interferon (TRIF), function upstream of RIPK3, interacting with RIPK3 via their RHIM domains to mediate necroptosis in response to viral infections and TLR signaling, respectively.…”
Section: Introductionmentioning
confidence: 99%